Konsep Kesetaraan Pendidikan Perempuan Perspektif Pemikiran KH. Hasyim Asy'ari - Lestari, Rini Eka; Wardan, Khusnul; Zaman, Nurul (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2025)
The concept of women’s education according to KH. Hasyim Asy’ari asserts that both men and women have equal rights to access education without distinction. This study aims to explore the concept of educational equality for women in his thought and practice. Using a qualitative literature study, primary data were obtained from al-‘Alim wa al-Muta‘allim, while secondary data were drawn from journal articles and relevant literature. Data validity was ensured through source and technique triangulation, and content analysis was applied. The findings reveal that KH. Hasyim Asy’ari viewed women’s education not only as personal development but also as the foundation of civilization, since women play a vital role in shaping future generations. He regarded women as imad al-bilad (pillars of the nation), making education essential in forming their character. His efforts in advancing women’s education included giving attention to his daughters’ education, organizing majelis ta’lim for women, accommodating female students at Tebuireng Islamic boarding school, and proposing the establishment of schools or madrasahs for women.